Pemberdayaan Prospective Coffee Entrepreneur Melalui Transformasi Kopi Terpadu di Dusun Tlumpak, Kabupaten Semarang - Baswara, Satsya Yoga; Widhiastuti, Ratieh; Nurkhin, Ahmad; Narenda, Alfa; Rifai, Achmad; Niam, Sufa’ah Hurumun; Ardyansyah, Faisal; Ali, Noor Faqih Udin; Salis, Abdul Rozaq (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This community service program aims to empower the Millennial Coffee Farmers Group (GAPOKTAN) in Tlumpak Hamlet, Semarang Regency, through integrated transformation in coffee management. Tlumpak Hamlet has abundant coffee resources. However, this abundant coffee resource potential is limited by the integrated roasting process, including post-harvest, roasting, marketing, and product legality. The main challenges faced by millennial coffee farmers are limited skills in using professional roasting machines, word-of-mouth sales, and the lack of a Home Industry Food Certificate (SPP-IRT). The implemented solution encompasses three crucial aspects: (1) Production Technology: Professional training in coffee roasting to create specialty coffee with the distinctive flavor of Tlumpak Hamlet, supported by a partnership with the Coffee Factory Community (KnK). (2) Marketing: Digital branding development through the creation of social media accounts, websites, and e-commerce platforms to expand market reach and increase sales. (3) Business Management: Assistance with SPP-IRT and halal certification applications to improve product legality and competitiveness. Implementation methods include education, training, and intensive, participatory mentoring. Expected outcomes are significant improvements in roasting skills (target 80%), increased sales through digital platforms (target 80%), and obtaining official government certification. Mandatory service outputs include publications in accredited national journals, media reports, activity videos, Copyright, and Implementation Agreements. This program is expected to transform farmers into independent, competitive coffee entrepreneurs and contribute to sustainable local economic development.